2021
DOI: 10.3892/etm.2021.10092
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis and competing endogenous RNA network in the human endometrium between proliferative and mid‑secretory phases

Abstract: Successful embryo implantation is the first step for establishing natural pregnancy and is dependent on the crosstalk between the embryo and a receptive endometrium. However, the molecular signaling events for successful embryo implantation are not entirely understood. To identify differentially expressed transcripts [long-noncoding RNAs (lncRNAs), microRNAs (miRNAs) and mRNAs] and competing endogenous RNA (ceRNA) networks associated with endometrial receptivity, the current study analyzed gene expression prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
2
11
0
Order By: Relevance
“…Previously, we performed next-generation sequencing to identify RNAs and non-coding RNAs related to embryo-implantation receptivity and found that miR-182-5p was more highly expressed in the proliferative phase than in the secretory phase during the endometrial receptivity period [ 16 ]. To validate the differential expression of miR-182-5p, we quantified miR-182-5p in the proliferative and secretory phases of normal endometrium tissues and during the secretory phase of infertility ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we performed next-generation sequencing to identify RNAs and non-coding RNAs related to embryo-implantation receptivity and found that miR-182-5p was more highly expressed in the proliferative phase than in the secretory phase during the endometrial receptivity period [ 16 ]. To validate the differential expression of miR-182-5p, we quantified miR-182-5p in the proliferative and secretory phases of normal endometrium tissues and during the secretory phase of infertility ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…In some cancers, miR-182 promotes tumor metastasis by upregulating epithelial–mesenchymal transition (EMT)-related genes [ 10 , 11 , 12 , 13 , 14 , 15 ]. We previously reported that miR-182 was downregulated in the mid-secretory phase, between 20 and 24 days of the menstrual cycle, during the window of implantation (WOI) in the endometrium [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human endometrium is a highly self-renewing tissue that is periodically shed, repaired, regenerated and remodeled, under the coordination of estrogen and progesterone, in preparation for embryo implantation [ 18 ]. Recently published studies analyzed the gene expression profiles between proliferative and mid-secretory endometria in fertile women, DEGs upregulated in the proliferative endometrium were significantly enriched in cell cycle, whereas downregulated DEGs were significantly enriched in immune system process and immune response [ 19 ]. The proliferative phase, which occurs following menstruation and precedes ovulation, is marked by the active growth of several cell types including HESCs, epithelial, and endothelial cells [ 20 ], and by ovulation, the average thickness of the endometrium reached about 12 mm, while during the luteal phase, endometrial growth tends to plateau and turned to differentiation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of progesterone in the post-ovulatory phase modulate the endometrial gene expression required for implantation by regulating DNA methylation [75][76][77], and alterations in the DNA methylation of 448 sites have been associated with defective endometrial receptivity and consequently in recurrent pregnancy failure [75,78]. Moreover, different non-coding transcripts like lncRNAs and miRNAs are involved in endometrial receptivity regulation [79].…”
Section: Pre-receptive and Receptive Endometriummentioning
confidence: 99%